'High' risk? A systematic review of the acute outcomes of mixing alcohol with energy drinks. (14th July 2014) - Peacock, Amy; Pennay, Amy; Droste, Nicolas; Bruno, Raimondo; Lubman, Dan I.
Abstract Aims Alcohol mixed with energy drinks (AmED) is a relatively new consumption trend generating increasing concern regarding potential adverse effects. Despite the political and health imperative, there has been no systematic and independent synthesis of the literature to determine whether or not AmED offers additional harms relative to alcohol. The aim of this study was to review the evidence about whether co‐consumption of energy drinks and alcohol, relative to alcohol alone, alters: (i) physiological, psychological, cognitive and psychomotor outcomes; (ii) hazardous drinking practices; and (iii) risk‐taking behaviour. Methods Pubmed, PsycInfo and Embase databases were searched until May 2013 for papers outlining descriptive, observational analytical and human experimental studies which compared target outcomes for AmED versus alcohol consumers (between‐subjects), or AmED versus alcohol consumption (within‐subjects). Odds ratios were calculated for target outcomes following screening, data extraction and quality assessment. Results Data were extracted from 19 papers. Analyses typically revealed increased odds of self‐reported stimulation‐based outcomes and decreased odds of sedation‐based physiological and psychological outcomes relative to when alcohol was consumed alone, as indicated by rigorous cross‐sectional descriptive research. These findings typically have not been reflected in experimental research, due possibly to the low doses administered relative to typical self‐reported 'real‐life' intake. AmED consumers generally report more hazardous alcohol consumption patterns and greater engagement in risk‐taking behaviour than alcohol consumers. While most studies had equivocal findings, two studies showed lower odds of risk‐taking behaviour for AmED relative to alcohol drinking sessions but limitations with respect to the outcome measures used restrict conclusions with regard to the behavioural outcomes of AmED use. Conclusions Mixing alcohol with energy drinks may exert a dual effect, increasing stimulation‐based effects and reducing sedation‐based outcomes; the clinical severity and dose threshold has not been established. At this stage it is unclear whether these changes in the nature of intoxication translate into greater alcohol intake and risk‐taking behaviour.